1982
DOI: 10.1016/s0006-3495(82)84497-4
|View full text |Cite
|
Sign up to set email alerts
|

Voltage independence of an electrotonic synapse

Abstract: the description of electrotonic coupling between 'lateral axons of the crayfish nerve cord (Watanabe and Grundfest, 'l961),-this synapse has shown no sign of being other than a linear current pathway. Electrotonic junctions from other systems studied over a period of many years also 'behave as linear pathways: pancreatic acinar cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
(2 reference statements)
3
7
0
Order By: Relevance
“…4B), whereas, at higher transjunctional potentials, the conductance of Px1͞Px2 channels displayed only a very modest reduction (Ϸ15%) of the initial values (Fig. 4C), which was similar to what was reported for crayfish septate junctions (34) and human Cx31.9 (32). Although it has been reported that junctional currents measured in insect cells are sensitive to changes in membrane potential (35), the relative voltage insensitivity of pannexin intercellular channels with polarization of one cell is a strong indication that polarization of both cells is not likely to affect significantly junctional conductance.…”
Section: Functional Expression In Paired Xenopussupporting
confidence: 87%
“…4B), whereas, at higher transjunctional potentials, the conductance of Px1͞Px2 channels displayed only a very modest reduction (Ϸ15%) of the initial values (Fig. 4C), which was similar to what was reported for crayfish septate junctions (34) and human Cx31.9 (32). Although it has been reported that junctional currents measured in insect cells are sensitive to changes in membrane potential (35), the relative voltage insensitivity of pannexin intercellular channels with polarization of one cell is a strong indication that polarization of both cells is not likely to affect significantly junctional conductance.…”
Section: Functional Expression In Paired Xenopussupporting
confidence: 87%
“…Rather, we favour the notion that this rarely observed slowly developing current reflects variations in the junctional current itself due to uncontrolled environmental factors such as temperature (Harris, Spray & Bennett, 1980;Jaslove & Brink, 1986) which may affect the gap junction permeability (Spray, White, Campos de Carvalho, Harris & Bennett, 1984) and/or kinetics. (Auerbach & Bennett, 1969) Yes Comparison with other voltage-controlled gap junctions Junctional channels controlled by potential are present mainly during embryonic stages while in adult tissues, voltage dependence of gap junctions is uncommon (Johnston & Ramon, 1982;Verselis & Brink, 1984;White, Spray, Schwartz, Wittenberg & Bennett, 1984;Spray, Ginzberg, Morales, Bennett, Babayastky, Gatmaitin & Arias, 1984;Bodmer & Spray, 1985;Weingart, 1986) and so far has been found to occur only between neurones. The voltage-dependent properties of the gap junctions studied to date are summarized in Table 2, which shows that channels at the crayfish rectifying synapse share some characteristics with those of amphibian embryonic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gap junctions between rat neonatal cardiac myocytes (Rook et al, 1988), rat hepatocytes (Spray et al, 1990) and Xenopus oocytes expressed from connexin 32 or 26 cRNA (Barrio et al, 1990) were more recently reported to display voltage dependence of the transjunctional type. Gap junctions in many other preparations have little if any voltage dependence, including crayfish (Johnston and Ramon, 1982) and earthworm septate axons (Verselis and Brink,…”
Section: Introductionmentioning
confidence: 99%